Drosophila Neuronal Injury Follows a Temporal Sequence of Cellular Events Leading to Degeneration at the Neuromuscular Junction. - Lincoln, B.L.; Alabsi, S.H.; Frendo, N.; Freund, R.; Keller, L.C. (Journal of experimental neuroscience, 2015)
Neurodegenerative diseases affect millions of people worldwide, and as the global population ages, there is a critical need to improve our understanding of the molecular and cellular mechanisms that drive neurodegeneration. At the molecular level, neurodegeneration involves the activation of complex signaling pathways that drive the active destruction of neurons and their intracellular components. Here, we use an in vivo motor neuron injury assay to acutely induce neurodegeneration in order to follow the temporal order of events that occur following injury in Drosophila melanogaster. We find that sites of injury can be rapidly identified based on structural defects to the neuronal cytoskeleton that result in disrupted axonal transport. Additionally, the neuromuscular junction accumulates ubiquitinated proteins prior to the neurodegenerative events, occurring at 24 hours post injury. Our data provide insights into the early molecular events that occur during axonal and neuromuscular degeneration in a genetically tractable model organism. Importantly, the mechanisms that mediate neurodegeneration in flies are conserved in humans. Thus, these studies have implications for our understanding of the cellular and molecular events that occur in humans and will facilitate the identification of biomedically relevant targets for future treatments.